Association between nutritional status, deficiency of protein, iron and vitamins, caloric intake and food security in Mexican school children - Housni, Fatima Ezzahra; Saenz Pardo Reyes, Erika; López Larios, Madeline de Jesús; Llanes Cañedo, Claudia; Aguilera Cervantes, Virginia Gabriela; Lares-Michel , Mariana (Progress in Nutrition, 2022)
The double burden of malnutrition, characterized by prevalence of undernutrition that coexist with overweight and obesity, affects more than a third of the Mexican child population. These conditions are linked to problems related to energy, macro and micronutrient deficiencies and in the contexts of poverty in Mexico, they are also related to Food Insecurity (FI). Therefore, the objective of this study is to explore the association between nutritional status, protein, iron and vitamin deficiency, caloric intake and Food Security (FS) in Mexican school children. 719 children between 5 and 12 years old from Chihuahua, Mexico were evaluated. Body Mass Index (BMI), weight for age (W/A), weight for height (W/H), height for age (H/A) and arm circumference (AC) were used. Two 24-hour recalls (R24), a Food Consumption Frequency Questionnaire (FQFC) and the Mexican Food Security Scale (EMSA) were applied. In addition, clinical evaluation of macro and micronutrient deficiencies was carried out. To examine the association between the variables, binary logistic regression models were performed reporting Odds Ratios (OR). Protein and micronutrient deficiencies were associated with the risk of both malnutrition and overweight and obesity. 71.4% of the overweight and obese children presented some degree of FI. Exceeding the consumption of fruits, vegetables, and soft drinks was associated with the risk of developing overweight and obesity. Micronutrient deficiencies and FI are not exclusive to undernutrition and are strongly associated with overweight and obesity problems. Exceeding the consumption of foods, even if they are healthy, is related to the risk of developing overweight and obesity.